The Uses of Balau Among the Melanau Community Especially in The Traditional Healing Rituals - Muhammad Faiz, Arshad; Ahmad Nizar, Yaakub; Mohamad Suhaidi, Salleh; Siti Zanariah, Ahmad Ishak (Secholian Publication, 2023)
Indigenous Knowledge is defined by UNESCO as the understandings, skills and philosophies that is formed by communities through a continuous interaction between the natural surroundings with its people. The traditions and customs of indigenous knowledge particularly traditional healing rituals within the Melanau community are being forgotten as they are less practice nowadays. Balau or scientifically known as mextroxylon sagu is a plant that is closely related to the traditional healing practice and the way of life of the Melanau community. The objectives of the paper are: to identify the uses of balau among the Melanau community and to analyse the types and practices of Melanau traditional healing rituals. This paper uses a qualitative approach which includes in- depth interview and observation to gather all the data. The findings of this paper are: there are many functions of balau in the daily use of the Melanau community as a source of food, income and healing; and there are several types of traditional healing rituals that already not practice by the Melanau community due to the availability of modern medicine and religious conversion. To preserve the practices of indigenous knowledge mainly traditional healing rituals are challenging due to the rapid modernization.